North America. - Bartholomew, John, 1831-1893 (W. & R. Chambers, 1868)
Map shows British America, Greenland, the United States, Mexico, Central America, and the "West India Is."; Alaska is shown as "United States Territory"; railroad lines shown only across Isthmus of Panama. Relief shown by hachures. Includes distances to China and Liverpool. Scale [ca. 1:33,800,000].